ID 156 – Prolonged inhibitory effect of 1 Hz rTMS of the motor cortex on the nociceptive evoked potentials to contralateral hand stimulation. Issue 3 (March 2016) - Testani, E.; Granata, G.; Pazzaglia, C.; Padua, L.; Valeriani,
Abstract : High frequency motor cortex rTMS produces an inhibitory effect on pain, however there are only few data about the effect of low frequency motor cortex rTMS on clinical and experimental pain. Since low frequency rTMS should have an inhibitory effect on motor cortex, whose activation reduces experimental pain, one could expect that 1 Hz motor cortex rTMS increases objective pain measures, such as laser evoked potentials (LEPs). In 8 healthy subjects, we investigated the effect of 1 Hz rTMS of left motor cortex on LEPs to stimulation of both right and left hand dorsum. LEPs were recorded at 4 different times: baseline, Time 0 (immediately after 20 min of 1 Hz rTMS), Time +20 (20 min after 1 Hz rTMS), Time +40 (40 min after 1 Hz rTMS). rTMS modified the amplitude of N2/P2 LEP component only to right hand stimulation ( F  = 12.06, p  < 0.001), while there was no effect on left hand LEPs ( F  = 0.7, p  = 0.56). Post-hoc analysis showed that the N2/P2 amplitude was reduced at Time 0, Time +20, and Time +40, as compared to baseline ( p  < 0.01). Conversely of what expected, 1 Hz rTMS of the motor cortex inhibits contralateral pain; this effects last up to 40 min after the cortical stimulation.